Искусство квилинга: магия бумажных лент / Анна Зайцева - Зайцева Анна Анатольевна (Азбука рукоделия, 2013)
Экземпляры: ф.5 (2013) / Инвентарный номер: 49872 / Цена: / Сис.шифр: 37.248 / Авт.знак: З-17 / ГРНТИ: 18.31.51 / ББК: 37.248